Transformation to a market economy in Eastern Europe, the former Soviet Union and Asia - Marangos, John (2004)
Introduction -- Inconsistencies in the transition processes -- Lack of institutions and rise of corruption and crime in transition economies -- Alternative transition processes -- Conclusion.
Photocopy.
Source: O'Hara, Phillip Anthony. Global political economy and the wealth of nations : performance, institutions, problems, and policies. London : Routledge, 2004. pp. [103]-126.
Includes bibliographical references (p. 123-126)
Keywords: Business enterprises -- Europe, Eastern; Structural adjustment (Economic policy) -- Europe, Eastern; Business enterprises -- Soviet Union; Structural adjustment (Economic policy) -- Soviet Union; Business enterprises -- Asia; Structural adjustment (Economic policy) -- Asia; Europe, Eastern -- Economic policy -- 1989- .; Soviet Union -- Economic policy -- 1989- .; Asia -- Economic policy -- 1989- .